Evolution of Educational Reforms in Bangladesh: A Comparative Study of National Education Commissions (1972-2009) - Ahmed, Rashed (RADINKA JAYA UTAMA PUBLISHER, 2024)
This commission laid the groundwork for subsequent reforms to promote universal primary education and reduce disparities in access. Following this, the 1982 Commission emphasized quality and relevance in education, advocating for a curriculum that aligned with the needs of the country’s economy and society. It introduced vocational training to bridge the gap between education and employment, highlighting the importance of skill development in achieving economic growth. This approach aimed to enhance accountability and responsiveness to the unique needs of different communities. In the early 2000s, the 2000 Education Commission further advanced the agenda of inclusive education, with a strong emphasis on gender equity and the need to support marginalized groups. It recognized the role of technology in modern education and recommended integrating ICT into the curriculum to prepare students for a globalized world. Finally, the 2009 Commission built upon previous recommendations and emphasized the necessity for ongoing reforms to adapt to changing global trends, including the need for a lifelong learning framework. Overall, the comparative analysis of these commissions highlights a continuous evolution of educational policies in Bangladesh, marked by an increasing recognition of the importance of quality, inclusivity, and relevance in education. It underscores the dynamic interplay between education and national development, as each commission responded to the pressing needs of its time while laying the groundwork for future reforms. This comprehensive examination of educational reforms serves as a crucial foundation for understanding the ongoing challenges and opportunities within the Bangladeshi education system today.